Effects of Saccharomyces cerevisiae-lactic acid bacteria cocultured maize silage on dairy cows performance and in vitro rumen fermentation - Chen, Q.; Liu, Z.; Zhou, C.; Zhong, Z.; Wu, J.; Jiang, A.; Yang, H.; Tan, Z.; Lukuyu, Ben A.; Kang, J. (Frontiers Media, 2026)
Introduction: Microbial additives can improve silage quality in lowland areas. However, Saccharomyces cerevisiae and Lactic Acid Bacteria efficacy on whole-plant maize silage under Tibet’s hypoxic and cold environment, have not been explored.